Postural deformities in congenital nephrotic syndrome. Issue 12 (December 1981) - Morgan, G; Postlethwaite, R J; Lendon, M; Houston, I B; Savage, J M
Abstract : Six successive cases of congenital nephrotic syndrome are described. Each one showed flexion deformities of the knees and hips, widely open anterior and posterior fontanelles, and wide separation of the skull sutures. These abnormalities were present not only in cases in which the renal histology was of the microcystic Finnish type of congenital nephrotic syndrome, but also in those in which the histological picture was one of the variants associated with congenital nephrotic syndrome. It is suggested that such abnormalities are postural deformities, possibly produced by the large placenta.